Common Genetic Variant Risk Score Is Associated With Drug-Induced QT Prolongation and Torsade de Pointes Risk: A Pilot Study. Issue 14 (4th April 2017) - Strauss, David G.; Vicente, Jose; Johannesen, Lars; Blinova, Ksenia; Mason, Jay W.; Weeke, Peter; Behr, Elijah R.; M. Roden, Dan; Woosley, Ray; Kosova, Gulum; Rosenberg, Michael A.; Newton-Cheh, Christopher
Abstract : Background: Drug-induced QT interval prolongation, a risk factor for life-threatening ventricular arrhythmias, is a potential side effect of many marketed and withdrawn medications. The contribution of common genetic variants previously associated with baseline QT interval to drug-induced QT prolongation and arrhythmias is not known. Methods: We tested the hypothesis that a weighted combination of common genetic variants contributing to QT interval at baseline, identified through genome-wide association studies, can predict individual response to multiple QT-prolonging drugs. Genetic analysis of 22 subjects was performed in a secondary analysis of a randomized, double-blind, placebo-controlled, crossover trial of 3 QT-prolonging drugs with 15 time-matched QT and plasma drug concentration measurements. Subjects received single doses of dofetilide, quinidine, ranolazine, and placebo. The outcome was the correlation between a genetic QT score comprising 61 common genetic variants and the slope of an individual subject's drug-induced increase in heart rate–corrected QT (QTc) versus drug concentration. Results: The genetic QT score was correlated with drug-induced QTc prolongation. Among white subjects, genetic QT score explained 30% of the variability in response to dofetilide ( r =0.55; 95% confidence interval, 0.09–0.81; P =0.02), 23% in response to quinidine ( r =0.48; 95% confidence interval, −0.03 to 0.79; P =0.06), and 27% in response to ranolazine ( r =0.52; 95% confidence interval, 0.05–0.80; P =0.03). Furthermore, the genetic QT score was a significant predictor of drug-induced torsade de pointes in an independent sample of 216 cases compared with 771 controls ( r 2 =12%, P =1×10 −7 ). Conclusions: We demonstrate that a genetic QT score comprising 61 common genetic variants explains a significant proportion of the variability in drug-induced QT prolongation and is a significant predictor of drug-induced torsade de pointes. These findings highlight an opportunity for recent genetic discoveries to improve individualized risk-benefit assessment for pharmacological therapies. Replication of these findings in larger samples is needed to more precisely estimate variance explained and to establish the individual variants that drive these effects. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01873950. Abstract : Supplemental Digital Content is available in the text.